Genomic Analysis of Staphylococcus aureus of the Lineage CC130, Including mecC-Carrying MRSA and MSSA Isolates Recovered of Animal, Human, and Environmental Origins - Gómez, Paula; Ruiz-Ripa, Laura; Fernández-Fernández, Rosa; Gharsa, Haythem; Ben Slama, Karim; Höfle, Ursula; Zarazaga, Myriam; Holmes, Mark A.; Torres, Carmen (Frontiers in Microbiology, 2021)
Most methicillin resistant Staphylococcus aureus (MRSA) isolates harboring mecC gene belong to clonal complex CC130. This lineage has traditionally been regarded as animal-associated as it lacks the human specific immune evasion cluster (IEC), and has been recovered from a broad range of animal hosts. Nevertheless, sporadic mecC-MRSA human infections have been reported, with evidence of zoonotic transmission in some cases. The objective of this study was to investigate the whole-genome sequences of 18 S. aureus CC130 isolates [13 methicillin-resistant (mecC-MRSA) and five methicillin-susceptible (MSSA)] from different sequences types, obtained from a variety of host species and origins (human, livestock, wild birds and mammals, and water), and from different geographic locations, in order to identify characteristic markers and genomic features. Antibiotic resistance genes found among MRSA-CC130 were those associated with the SSCmecXI element. Most MRSA-CC130 strains carried a similar virulence gene profile. Additionally, six MRSA-CC130 possessed scn-sak and one MSSA-ST130 had lukMF’. The MSSA-ST700 strains were most divergent in their resistance and virulence genes. The pan-genome analysis showed that 29 genes were present solely in MRSA-CC130 (associated with SCCmecXI) and 21 among MSSA-CC130 isolates (associated with phages). The SCCmecXI, PBP3, GdpP, and AcrB were identical at the amino acid level in all strains, but some differences were found in PBP1, PBP2, PBP4 and YjbH. An examination of host markers showed that the 3' region of the bacteriophage φ3 was nearly identical to the reference sequence. Truncated hlb gene was also found in scn-negative strains (two of them carrying sak-type gene). The dtlB gene of wild rabbit isolates included novel mutations. The vwbp gene was found in the three MSSA-ST700 strains from small ruminants and in one MSSA-ST130 from a red deer; these strains also carried a scn-type gene, different from the human and equine variants. Finally, a phylogenetic analysis showed that the three MSSA-ST700 strains and the two MSSA-ST130 strains cluster separately from the remaining MRSA-CC130 strains with the etD2 gene as marker for the main lineage. The presence of the human IEC cluster in some mecC-MRSA-CC130 strains suggests that these isolates may have had a human origin.